Answer
Verified
430.2k+ views
Hint:Here we will use the concepts of the algebra and the arithmetic equations. Also, we will concentrate on the reasoning and the calculus. Remember the slope of the two parallel lines are always equal.
Complete step by step solution:
A line which is parallel to the given line is $x - 2y = 2$ must have the same slope. Comparing the given equation with the standard line equation: $y = mx + c$
Take the given expression: $x - 2y = 2$
Convert the above equation in the form of the standard equation.
$ - 2y = 2 - x$
Taking constant on the opposite side.
$ \Rightarrow y = - 1 + \dfrac{x}{2}$
So, the slope of the given line is equal to $\dfrac{1}{2}$
Now, the slope of the tangent line can be derived using the derivation.
Now, the given expression is $y = \dfrac{{x - 1}}{{x + 1}}$ …(A)
So, here we will apply $\left( {\dfrac{u}{v}} \right)$rule to find the derivation.
$y' = \dfrac{{x(x - 1) - (x - 1).1}}{{{{\left( {x + 1} \right)}^2}}}$
Simplify the above equation, like terms with the same value and the opposite sign cancel each other.
$y' = \dfrac{2}{{{{\left( {x + 1} \right)}^2}}}$
Now, to find the value of “x”, take $y' = \dfrac{1}{2}$ in the above equation.
$\dfrac{1}{2} = \dfrac{2}{{{{\left( {x + 1} \right)}^2}}}$
Take cross multiplication, where the numerator of one side is multiplied with the denominator of the opposite side and vice-versa.
$ \Rightarrow {(x + 1)^2} = 4$
Take the square root on both the sides of the equation.
$ \Rightarrow \sqrt {{{(x + 1)}^2}} = \sqrt 4 $
Square and square root cancel each other on the left hand side of the equation.
$ \Rightarrow x + 1 = \pm 2$
So, $x + 1 = 2$ or $x + 1 = - 2$
When you move any term from one side of the equation to the other side, then the sign of the term changes. Positive terms become negative and vice-versa.
$ \Rightarrow x = 1$ or $x = ( - 3)$
Now, placing the values of “x” in the equation (A)
When $x = 1,$
$ \Rightarrow y = 0$
And when $x = ( - 3)$
$ \Rightarrow y = 2$
Therefore, the equation of the line $(1,0)$ with the slope $m = \dfrac{1}{2}$ and equation of the line through $( - 3,2)$ with the slope $m = \dfrac{1}{2}$ using the $y - {y_0} = m(x - {x_0})$
Which gives –
$y = \dfrac{1}{2}x + \dfrac{7}{2}$ and
$y = \dfrac{1}{2}x - \dfrac{1}{2}$
Note: Be careful about the sign convention and the simplification of the algebraic expressions. Always remember when you move any term from one side to another sign of the term changes. Positive terms become negative and vice-versa.
Complete step by step solution:
A line which is parallel to the given line is $x - 2y = 2$ must have the same slope. Comparing the given equation with the standard line equation: $y = mx + c$
Take the given expression: $x - 2y = 2$
Convert the above equation in the form of the standard equation.
$ - 2y = 2 - x$
Taking constant on the opposite side.
$ \Rightarrow y = - 1 + \dfrac{x}{2}$
So, the slope of the given line is equal to $\dfrac{1}{2}$
Now, the slope of the tangent line can be derived using the derivation.
Now, the given expression is $y = \dfrac{{x - 1}}{{x + 1}}$ …(A)
So, here we will apply $\left( {\dfrac{u}{v}} \right)$rule to find the derivation.
$y' = \dfrac{{x(x - 1) - (x - 1).1}}{{{{\left( {x + 1} \right)}^2}}}$
Simplify the above equation, like terms with the same value and the opposite sign cancel each other.
$y' = \dfrac{2}{{{{\left( {x + 1} \right)}^2}}}$
Now, to find the value of “x”, take $y' = \dfrac{1}{2}$ in the above equation.
$\dfrac{1}{2} = \dfrac{2}{{{{\left( {x + 1} \right)}^2}}}$
Take cross multiplication, where the numerator of one side is multiplied with the denominator of the opposite side and vice-versa.
$ \Rightarrow {(x + 1)^2} = 4$
Take the square root on both the sides of the equation.
$ \Rightarrow \sqrt {{{(x + 1)}^2}} = \sqrt 4 $
Square and square root cancel each other on the left hand side of the equation.
$ \Rightarrow x + 1 = \pm 2$
So, $x + 1 = 2$ or $x + 1 = - 2$
When you move any term from one side of the equation to the other side, then the sign of the term changes. Positive terms become negative and vice-versa.
$ \Rightarrow x = 1$ or $x = ( - 3)$
Now, placing the values of “x” in the equation (A)
When $x = 1,$
$ \Rightarrow y = 0$
And when $x = ( - 3)$
$ \Rightarrow y = 2$
Therefore, the equation of the line $(1,0)$ with the slope $m = \dfrac{1}{2}$ and equation of the line through $( - 3,2)$ with the slope $m = \dfrac{1}{2}$ using the $y - {y_0} = m(x - {x_0})$
Which gives –
$y = \dfrac{1}{2}x + \dfrac{7}{2}$ and
$y = \dfrac{1}{2}x - \dfrac{1}{2}$
Note: Be careful about the sign convention and the simplification of the algebraic expressions. Always remember when you move any term from one side to another sign of the term changes. Positive terms become negative and vice-versa.
Recently Updated Pages
10 Examples of Evaporation in Daily Life with Explanations
10 Examples of Diffusion in Everyday Life
1 g of dry green algae absorb 47 times 10 3 moles of class 11 chemistry CBSE
If the coordinates of the points A B and C be 443 23 class 10 maths JEE_Main
If the mean of the set of numbers x1x2xn is bar x then class 10 maths JEE_Main
What is the meaning of celestial class 10 social science CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
Which are the Top 10 Largest Countries of the World?
How do you graph the function fx 4x class 9 maths CBSE
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
In the tincture of iodine which is solute and solv class 11 chemistry CBSE
Why is there a time difference of about 5 hours between class 10 social science CBSE